Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1136/annrheumdis-2013-204351
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and cardiovascular disease in systemic lupus erythematosus: effects of in vivo statin treatment

Abstract: Our overall data suggest that fluvastatin improves the impairment of a redox-sensitive pathway involved in processes that collectively orchestrate the pathophysiology of atherothrombosis in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 35 publications
5
36
0
3
Order By: Relevance
“…Лечение пациентов с СКВ флувастатином в течение 1 мес уменьшало индекс активности SLEDAI, уровень ли-пидов, окислительный стресс и сосудистое воспаление [37]. Терапия статинами в исследовании LUMINA (LXXVI) привела к существенному уменьшению индекса активности SLAM-R и значительному клиническому улучшению у пациентов с СКВ [89].…”
Section: о б з о р ыunclassified
See 2 more Smart Citations
“…Лечение пациентов с СКВ флувастатином в течение 1 мес уменьшало индекс активности SLEDAI, уровень ли-пидов, окислительный стресс и сосудистое воспаление [37]. Терапия статинами в исследовании LUMINA (LXXVI) привела к существенному уменьшению индекса активности SLAM-R и значительному клиническому улучшению у пациентов с СКВ [89].…”
Section: о б з о р ыunclassified
“…Имеющиеся данные показали, что применение флувастатина у больных СКВ, по-видимо-му, подавляет окислительно-воспалительные механизмы, вовлеченные в развитие атерогенеза [37].…”
Section: о б з о р ыunclassified
See 1 more Smart Citation
“…SLE monocytes are more prone to oxidative damage (63)* and there is evidence for increases in macrophage proinflammatory subsets M1 and M2b, and decreases in the anti-inflammatory M2a and M2c populations in SLE, which may contribute to inflammation. (64) IFNs drive macrophages to engulf lipids,(48) and enhanced monocyte migration to plaque site increases foam cell production.…”
Section: Pathogenesis Of Premature Atherosclerosis In Slementioning
confidence: 99%
“…(86) Fluvastatin had anti-inflammatory effects on SLE macrophages, lowering ROS production. (63)* A recent study suggested that statin therapy in Taiwanese SLE patients with hyperlipidemia may reduce the risk of mortality, CVD and end-stage renal disease. (94)** As we learn more about the shared pathogenesis of these inflammatory conditions, perhaps specific statin and patient selection will yield greater improvement in CV risk for SLE patients.…”
Section: Pathogenesis Of Premature Atherosclerosis In Slementioning
confidence: 99%